2021
DOI: 10.3390/ma14071791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3D Printing-Line Directions for Stretchable Sensor Performances

Abstract: Health monitoring sensors that are attached to clothing are a new trend of the times, especially stretchable sensors for human motion measurements or biological markers. However, price, durability, and performance always are major problems to be addressed and three-dimensional (3D) printing combined with conductive flexible materials (thermoplastic polyurethane) can be an optimal solution. Herein, we evaluate the effects of 3D printing-line directions (45°, 90°, 180°) on the sensor performances. Using fused fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The lack of enhancement is related to the presence of CNTs F I G U R E 5 (A) Characterization of multi-axis 3D force sensor 125 ; (B) The sensors tracked human movements 126 ; (C) The sensor demonstrated the ability to detect finger-bending motion. 127 and is associated with two primary factors: the poorer spreadability of the restricted processing window of substrate limiting the diffusion process between the different layers (owning to the different crystallization temperatures) and the composite compared to the pure polymer (owning to the higher melt-in-fluid index (MFI)). The increase in CNTs content results in a severe decrease in MFI, [121][122][123] which explains the nozzle obstruction issue that occurs when printing with filaments that have a high MWCNTs filling rate.…”
Section: Performance Of Cntsreinforced Pmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of enhancement is related to the presence of CNTs F I G U R E 5 (A) Characterization of multi-axis 3D force sensor 125 ; (B) The sensors tracked human movements 126 ; (C) The sensor demonstrated the ability to detect finger-bending motion. 127 and is associated with two primary factors: the poorer spreadability of the restricted processing window of substrate limiting the diffusion process between the different layers (owning to the different crystallization temperatures) and the composite compared to the pure polymer (owning to the higher melt-in-fluid index (MFI)). The increase in CNTs content results in a severe decrease in MFI, [121][122][123] which explains the nozzle obstruction issue that occurs when printing with filaments that have a high MWCNTs filling rate.…”
Section: Performance Of Cntsreinforced Pmcsmentioning
confidence: 99%
“…(Figure 5B). Vu et al 127 printed tensile sensors of CNTs/TPU composites using the FDM printing process. Their sensors exhibited excellent stability of 10,000 cycles and a fast response time of 120 ms.…”
Section: Carbon‐reinforced Pmcs and Their Applicationsmentioning
confidence: 99%
“…The performance of the sensor (such as gauge factor and linearity) can be controlled by printing parameters during the fabrication process. 45 These parameters are the printing-line directions, 46 needle diameter, 47 ratio of components in the composites, 45 and printing speed. 45 Abshirini et al 47 fabricated highly flexible strain sensors by extrusion-based 3D printing.…”
Section: Additive Manufacturing Techniques and Processmentioning
confidence: 99%
“…The piezoresistive sensing mechanism depends on the MWNT network reorganization under external load and an appropriate amount of MWNTs resulted in an effective connection of MWNTs which consequently led to higher sensitivity to external loads. Vu et al 46 studied the effects of the printing-line directions (45°, 90°, 180°) on the performance of a strain sensor fabricated via the FDM method. The results showed that all three samples had acceptable performance in terms of sensitivity (GF) with the sample printed at 45° exhibiting the highest GF among the samples.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…The main characteristic of flexible TPU is high deformability. This, combined with the right architecture of the lattice material, can lead to high efficiency in energy absorption and crashworthiness, for example, 3D-printed flexible TPU-based lattice materials also have great potential in the fabrication of lightweight, custom-shaped structures and functional parts for applications in various fields such as aerospace engineering, medical devices and sports equipment [ 27 , 28 , 29 , 30 , 31 ]. The aim of this work is to present results regarding the mechanical response of 3D printed lattice structures made of flexible TPU subjected to static (tension, three-point bending, compression) and dynamic (dynamic mechanical thermal analysis) tests.…”
Section: Introductionmentioning
confidence: 99%